Nocturia in men and associated comorbidities: a southeast Michigan study - Daniel Fortney; Prasun Sharma; Alexander Geisenhoff; Bernadette M.M. Zwaans; Michael D Lutz (Journal of Men's Health, 2023)
Nocturia is a highly prevalent condition associated with poor quality of life and increased adverse health outcomes. Our study investigates the prevalent condition of nocturia and its profound impact on individuals’ quality of life and adverse health outcomes. We explore the correlation between nocturia and various comorbidities in a southeast Michigan population by analyzing data from 1023 participants who completed self-administered questionnaires during the 2021 Michigan Institute of Urology’s Men’s Health Event; 892 participants responded to the nocturia questionnaire. Categorizing participants based on the severity of nocturia into three groups—no nocturia, nocturia once per night, and multiple nocturia episodes per night—we employed Pearson’s Chi-square test to examine the relationship between nocturia severity and the presence of comorbidities. Our findings demonstrate significant associations between increasing episodes of nocturnal voids and the prevalence of hypertension, non-insulin-dependent diabetes and anxiety. Additionally, arthritis and colorectal polyps exhibit notable links with multiple nocturia episodes, while participants with a family history of hypertension show decreased prevalence as nocturnal voids increase, and a family history of myocardial infarction is notably associated with nocturia, particularly in the nocturia once per night group. Our research highlights the widespread impact of nocturia and its strong associations with diverse comorbidities, underscoring the importance of further investigation to comprehend the underlying mechanisms and enhance patient outcomes.